Observations of fine particulate nitrated phenols in four sites in northern China: concentrations, source apportionment, and secondary formation - L. Wang; L. Wang; X. Wang; R. Gu; H. Wang; L. Yao; L. Wen; F. Zhu; W. Wang; L. Xue; L. Yang; L. Yang; et al. (Atmospheric Chemistry and Physics, 2018)
Filter samples of fine particulate matters were collected at four sites in northern China (urban, rural, and mountain) in summer and winter, and the contents of nine nitrated phenols were quantified in the laboratory with the use of ultra-high-performance liquid chromatography coupled with mass spectrometry. During the sampling periods, the concentrations of particulate nitrated phenols exhibited distinct temporal and spatial variation. On average, the total concentration of particulate nitrated phenols in urban Jinan in the wintertime reached 48.4 ng m−3, and those in the summertime were 9.8, 5.7, 5.9, and 2.5 ng m−3 in urban Jinan, rural Yucheng and Wangdu, and Mt. Tai, respectively. The elevated concentrations of nitrated phenols in wintertime and in urban areas demonstrate the apparent influences of anthropogenic sources. The positive matrix factorization receptor model was then applied to determine the origins of particulate nitrated phenols in northern China. The five major source factors were traffic, coal combustion, biomass burning, secondary formation, and aged coal combustion plume. Among them, coal combustion played a vital role, especially at the urban site in the wintertime, with a contribution of around 55 %. In the summertime, the observed nitrated phenols were highly influenced by aged coal combustion plumes at all of the sampling sites. Meanwhile, in remote areas, contributions from secondary formation were significant. Further correlation analysis indicates that nitrosalicylic acids were produced mostly from secondary formation that was dominated by NO2 nitration.